Akuntansi Belis Dalam Adat Perkawinan di Desa Nelle Urung - Lambertus, Yohanes; Syukur, Felixius Kurniawan; Dairy, Maria Kristin Rezzavila; Ningsih, Katarina Wahu; Toji, Maria Selmiyati (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Penelitian ini mengkaji